Exploring the Regulatory Mechanism of CXCL16 Molecule-Related Antigen Presentation Using lncRNA-mRNA Co-Expression Network Analysis - Liu TT; Zheng S; Jia LX; Du J; Piao C (Journal of Inflammation Research)
Ting-ting Liu, Shuai Zheng, Li-xin Jia, Jie Du, Chunmei Piao Beijing Institute of Heart, Lung and Blood Vessel Diseases, The Key Laboratory of Remodeling Cardiovascular Diseases, Ministry of Education, Collaborative Innovation Center for Cardiovascular Disorders, Beijing Anzhen Hospital, Capital Medical University, Beijing, People’s Republic of ChinaCorrespondence: Chunmei Piao, Email pichm2@ccmu.edu.cnAim: To investigate the regulatory mechanism of CXCL16 molecule-related Aspergillus fumigatus (A.f.) extract-induced antigen presentation in a mouse asthma model based on the long non-coding RNA (lncRNA) and mRNA expression profile.Methods: CXCL16 knockout mice and wild-type mice were administered with A.f. extract by intratracheal instillations to induce asthma airway inflammation. High throughput chip sequencing was used to screen for lncRNA and mRNA expression profile differences in lung tissue between the groups. A lncRNA-mRNA co-expression network was constructed through gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis. Wild-type mice received intraperitoneal injections with CXCL16 neutralizing antibodies, and the bioinformatics and inflammation results were validated using RT-PCR and ELISA.Results: Compared with wild-type mice, CXCL16 knockout mice showed 120 lncRNA and 388 mRNA upregulated in lung tissue, while 1984 lncRNA and 301 mRNA were downregulated. The constructed lncRNA-mRNA co-expression network included 244 differentially expressed lncRNAs and 49 differentially expressed mRNAs. Among them, the core network’s expression of the hub gene Idh1 and the top four lncRNAs was validated in the CXCL16 neutralizing antibody asthma model.Conclusion: A comprehensive biological analysis of the lncRNA-mRNA co-expression network explored key genes and pathways, providing new insights for understanding their mechanisms and discovering new targets for asthma induced by A.f. The four differentially expressed key lncRNAs in the co-expression network (NONMMUT026034, NONMMUT028184, NONMMUT016537, and NONMMUT043155) can serve as intervention targets for CXCL16 molecular regulation of antigen presentation in mice asthma models.Keywords: Long non-coding RNA, CXCL16, antigen presentation, co-expression network, asthma